Exploring Equity in Higher Education Systems: Reflections from Argentina and Chile - Garcia, Ana Maria (2019)
Public debates on equity in higher education usually focus on the impact of admissions and funding policies on systems as a whole. More specifically, it is assumed that, first, the more selective the admission criteria and procedures are, the fewer the opportunities that lower-income students will have to access higher education. Second, the cost-sharing of undergraduate studies through tuition fees can reduce the chances of the less privileged social strata to pursue higher education studies. Although both premises are true, two additional factors can affect equity in higher education significantly: one, the capacity of the secondary and undergraduate levels to retain and provide high-quality education to lower-income and culturally disadvantaged students; and two, the institutional differentiation, which results in vertical stratification in terms of status, with lower-income students attending low-quality institutions.